1954
DOI: 10.2151/jmsj1923.32.4_85
|View full text |Cite
|
Sign up to set email alerts
|

An Aerological Study on the Pre-summer Rainy Season in Japan

Abstract: The amount of precipitation is examined in relation to the upper wind field and temperature field in the pre-summer rainy season in Japan,, June and July, for the years 1950 and 1951. It may be well explained as a result of vertical motions of baroclinic unstable waves in the westerlies. In the atmospheric structure during this season, there can be found a similarity to the structure of baroclinic unstable wave.It is found from the data of 1946, 1950 and 1951 that the horizontal distribution of the mean zonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1958
1958
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, further studies are necessary, in order to clarify the problems relating to the subject. There are many studies on the Bai-u pheno menon, a large number of which particularly focus on the divisions within the Bai-u season (MATSUMOTO et al, 1954;YOSHINO,1965;MIZUKOSHI, 1986). Before going on to comparisons, it should be noted that, where the criteria for the division of the Bai-u season, considered space-scale and meteorological elements are concerned, the pres ent study differs from other studies on a similar subject.…”
Section: Periodicities In the Bai-u Seasonmentioning
confidence: 99%
“…However, further studies are necessary, in order to clarify the problems relating to the subject. There are many studies on the Bai-u pheno menon, a large number of which particularly focus on the divisions within the Bai-u season (MATSUMOTO et al, 1954;YOSHINO,1965;MIZUKOSHI, 1986). Before going on to comparisons, it should be noted that, where the criteria for the division of the Bai-u season, considered space-scale and meteorological elements are concerned, the pres ent study differs from other studies on a similar subject.…”
Section: Periodicities In the Bai-u Seasonmentioning
confidence: 99%
“…A similar wet season in southern China is associated with distur-bances in the form of velocity convergences in the monsoonal southwesterly currents 12 ). It has been suggested that the Baiu rains are heavier over Japan when a single jet prevails and less when there is a double jet 13 . In other words, when the confluence of the summer East-Asian jets occurs to the west of Japan, usually over the margins of the continent, Baiu rains are abnormally heavy, and when the confluence occurs farther to the east, over the western Pacific, the rains are less abundant.…”
Section: Figmentioning
confidence: 99%